Restruccion del area y propuesta del nuevo proceso de servicio al cliene de la ilustre municipalidad del empalme como mecanismo de incremento en las recaudaciones municipales periodo 2010 2015 - Orellana Morales, Manuel Rodolfo (2011)
The modernization of public administration has led to the evaluation of the quality of service becomes a useful tool, whose use has increased considerably in the past years. This reality, however, is not homogeneous either in terms of local geography, or in relation to models of processes that are implemented and even, neither is in the degree of development reached by the various municipalities. The administrative systems that govern the lives of the vast majority of municipalities in our country are in the process of learning, concerned with establishing the fundamental mechanisms for public management have to ensure coverage of services, not to institute models of care who seek quality, timeliness and satisfaction of the citizen. The lack of quality management focused on customer service in the City of Junction has generated revenues to become increasingly difficult and therefore the municipality's public works are also affected, and although the implementation of management systems quality is the implementation in an organization of the principles of total quality, but there is no unique method to implement. For this specific problem raises a logical framework matrix leading to a process to adopt management systems, quality customer service. Along these lines we will approach the reality of the Municipality of The Junction and the rationalization of activities that will lead to a renewed customer service to improve municipal collections.